Industri Film Indonesia : Membangun Keselarasan Ekonomi Media Film dan Kualitas Konten - Euis Komalawati (LUGAS Jurnal Komunikasi, 2017)
As an appreciation for creative works, the Indonesian Film Festival (FFI) and the Indonesian Film Appreciation (AFI) aimed at giving an award for the best work. The interesting part was the implementation of AFI 2015 emerged several award categories such as Appreciation for the Local Government and Film Criticism Appreciation. This occurred in the midst of concerns about the development of Indonesian film industries which tend to be stagnant. Film communities tried to give fresh ideas and break the film market. This new award can certainly be seen as an effort through the film festival program in spurring the film industries with creative work of educating the nation's children, especially film as a "cultural builder". Film is a cultural construction. In America, the country where the Hollywood film industry is the mecca of film generation, people still debate the cultural influence of Hollywood on social phenomena. Sociologist Norman Denzim said that drinking shows in US films have influenced the misleading romanticism of alcoholism in public consciousness (Vivian, 2008: 160). On the other hand, borrowing Adorno's term, the film has carried the culture industry powerless with market power. Discussing the media industry leads to the film media economy, as the focus of Indonesian filmmakers today. For most producers, award-winning films at international film festivals are "less meaningful" when they are not in box office positions. This paper proposed to reveal the economic attractiveness of the film media and the quality of Indonesian film content in accordance with the Republic of Indonesia Act. Number 33 of 2009 on Film. It stated that the film has a function: culture; education; entertainment; information; the driving force of creative work; and economy.